Facile synthesis of spherically SrWO4 nanomaterials via surfactant-assisted co-precipitation method: an affordable catalyst for the mitigation of carcinogenic organic dye. Issue 17 (23rd December 2022) - Arunpandian, M.; Sivaganesh, D.; Revathy, M. S.; Selvakumar, K.; Arunachalam, S.; Geetha, D.
ABSTRACT: In this scenario, a novel spherical like SrWO4 nanomaterial's were made by the simple co-precipitation route was confirmed by various characterisation techniques. The Powder X-Ray diffraction (P-XRD) was explained the crystalline nature of the as-prepared materials; the obtained diffraction peaks reveal good crystalline nature of as prepared novel SrWO4 nanomaterials. The Williamson-Hall (W-H) plot method was used to analyse the individual role of particle sizes and lattice strain on the peak broadening of the NPs of host and surfactant doped SrWO4 . The morphology of the host SrWO4 materials has been spherical, but also of surfactants, the morphology will be changed. The presenting elements and the oxidation state of Sr, O and W were confirmed by X-ray Photoelectron Spectroscopy analysis. Interestingly, SrWO4 .SDS+PVP catalyst having an efficient activity in the degradation process than that others and the degradation efficiency 95.7% corresponds to methylene blue (MB) degradation within 90 mins. In Reactive Oxidative Species study, hydroxyl and superoxide radical's quenchers are the main reactive species in the MB degradation process. On the other hand, the recycling test has confirmed the stability and reusability of the catalysts.